1995
DOI: 10.1063/1.868690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrated wall suction on a turbulent boundary layer

Abstract: The effect of suction, applied through a short porous wall strip, on a low Reynolds number self-preserving turbulent boundary layer has been quantified by measuring the local wall shear stress and the main Reynolds stresses downstream of the strip. When the suction rate is sufficiently high, pseudo-relaminarization occurs almost immediately downstream of the strip. Farther downstream, transition occurs followed by a slow return to a fully turbulent self-preserving state. During relaminarization, the measured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
77
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 12 publications
15
77
2
1
Order By: Relevance
“…The distance between the AFC section and the TE covers a distance of 5δ 0 and the results have shown that even in the case of modest flow suction, the flow does not recover to that of the baseline (σ = 0) case within this distance. This is in agreement with the findings of Antonia et al, 34 who reported that for σ = −2.6 the flow requires approximately 40δ 0 to return to its original state (x = 0, σ = 0). The treated profiles partially return to their original values in the near-wall region beyond the locations m2 and m4, which agrees with the findings of Park and Choi 35 and Antonia et al, 34 where the near-wall energy content of the streamwise velocity component was shown to return to its original value in near-wall energy content of the streamwise velocity component was shown to return to its original value in a short distance.…”
Section: -41 43 44supporting
confidence: 83%
See 4 more Smart Citations
“…The distance between the AFC section and the TE covers a distance of 5δ 0 and the results have shown that even in the case of modest flow suction, the flow does not recover to that of the baseline (σ = 0) case within this distance. This is in agreement with the findings of Antonia et al, 34 who reported that for σ = −2.6 the flow requires approximately 40δ 0 to return to its original state (x = 0, σ = 0). The treated profiles partially return to their original values in the near-wall region beyond the locations m2 and m4, which agrees with the findings of Park and Choi 35 and Antonia et al, 34 where the near-wall energy content of the streamwise velocity component was shown to return to its original value in near-wall energy content of the streamwise velocity component was shown to return to its original value in a short distance.…”
Section: -41 43 44supporting
confidence: 83%
“…This is in agreement with the findings of Antonia et al, 34 who reported that for σ = −2.6 the flow requires approximately 40δ 0 to return to its original state (x = 0, σ = 0). The treated profiles partially return to their original values in the near-wall region beyond the locations m2 and m4, which agrees with the findings of Park and Choi 35 and Antonia et al, 34 where the near-wall energy content of the streamwise velocity component was shown to return to its original value in near-wall energy content of the streamwise velocity component was shown to return to its original value in a short distance. The study also reported that as the turbulent structures were brought closer to the wall, the viscous dissipation increased downstream of the AFC treatment.…”
Section: -41 43 44supporting
confidence: 83%
See 3 more Smart Citations